Prevention of alcohol withdrawal seizures with oral diazepam loading - Devenyi, Paul (1985)
Twenty patients withdrawing from alcohol who had reliable histories of previous alcohol-withdrawal seizures and thus were at high risk for a subsequent seizure were treated in hospital with oral diazepam loading: 20 mg of the drug was given every hour to a minimum total of 60 mg. None of the patients had a seizure during the stay in hospital. We believe that phenytoin prophylaxis is not necessary in these circumstances. However, if the patient is already taking phenytoin, this drug should not be abruptly discontinued in the withdrawal period in favour of diazepam loading.